Balancing the exploitation-exploration paradox during major geopolitical disruptions: the importance of supply chain structural ambidexterity - Moradlou, Hamid; Skipworth, Heather; Bals, Lydia; Aktas, Emel; Roscoe, Samuel (Academy of Management, 2023)
We answer the question “How do companies develop and deploy supply chain structural ambidexterity to effectively manage geopolitical disruptions?” by investigating three significant geopolitical disruptions: Brexit, the US-China trade war, and the Covid-19 pandemic. We use an inductive theory-elaboration approach to build on Organisational Learning Theory and Dunning’s eclectic paradigm of international production. We conducted 29 elite interviews with senior supply chain executives across 14 multi-national manufacturing firms and validated the analysis by triangulating secondary data sources, including standard operating procedures, annual reports, and organizational protocols. When faced with significant geopolitical disruptions, companies develop and deploy supply chain structural ambidexterity by (1) developing parallel supply chains; (2) significantly reconfiguring their supplier networks, and (3) restructuring their internal sub-units. We contribute to Organisational Learning Theory and Dunning’s eclectic paradigm by empirically examining how companies reconfigure supply chains to pursue exploration and exploitation activities in response to geopolitical disruptions. During significant geopolitical disruptions, managers make decisions in tight timeframes. Therefore, we propose three types of supply chain structural ambidexterity based on the transition time available. We conclude with a managerial framework to assist firms in developing supply chain structural ambidexterity in response to geopolitical disruptions.